Development of Construction Project Monitoring Information System Public Utility Infrastructure at the Manado City Settlement Office - Hasiholan, Eugenia Marina Ceranie (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
Public Utility Infrastructure (PSU) activities at the Manado City Settlement Office are one of the strategic programs in the development of residential area infrastructure. Monitoring of PSU projects faces various challenges, such as scattered work locations, time constraints, and the absence of an integrated and spatial-based information system. This research aims to develop a PSU construction project monitoring information system that utilizes Geographic Information System (GIS) technology and the Microsoft Power Apps platform to support real-time and structured visualization of project locations and work progress. The development method used is Rapid Application Development (RAD), which allows system development to be carried out quickly and iteratively based on user needs. Primary data is obtained through interviews and observations in the field, while secondary data comes from technical documents on project planning and implementation. The results of the study show that the information system developed is able to present location data, field documentation, and work progress reporting spatially, accurately, and easily accessible to the Commitment Making Officer (PPK) and the Field Director. The presence of this system is expected to increase the effectiveness of project monitoring and support fast and appropriate decision-making in the implementation of PSU activities in Manado City.